The Role of Relaxin in Glycodelin Secretion1 - Stewart, Dennis R.; Erikson, Marlena S.; Erikson, Mark E.; Nakajima, Steven T.; Overstreet, James W.; Lasley, Bill L.; Amento, Edward P.; Seppala, Markku (The journal of clinical endocrinology and metabolism, 1997)
Glycodelin is a glycoprotein named for its unique carbohydrate structure. Glycodelin is produced by the secretory endometrium during the late luteal phase and returns to baseline during menses of the ensuing cycle, whereas in conceptive cycles it rapidly increases. Although progesterone and possibly estradiol are required for glycodelin production, they are not directly involved in the synthesis and release of this protein. Their role may be development of the endometrial secretory glandular elements, whereas other factors are required to initiate and maintain glycodelin secretion. The pattern of relaxin secretion during the luteal phase and early pregnancy is similar to that of glycodelin, but their profiles have not been determined simultaneously.To investigate the relationship of relaxin and glycodelin, two studies were conducted. In the first study, relaxin, glycodelin, and ovarian steroids were measured in daily serum samples from nonconceptive and conceptive natural cycles. Profiles of relaxin and glycodelin were closely associated, with the onset of relaxin preceding glycodelin secretion by 1–2 days in nonconceptive cycles, and the pregnancy-associated increases in each hormone differing by about 2 days. The second study tested the hypothesis that relaxin stimulates glycodelin secretion. Samples were obtained from patients injected with human relaxin for 28 days. In subjects demonstrating ovarian cyclicity, glycodelin secretion was elevated, but it was not detected in subjects without ovarian cyclicity or in placebo-treated control subjects.This study reveals a close temporal and quantitative relationship between relaxin and glycodelin profiles in the late luteal phase and early pregnancy. It also demonstrates that relaxin administration can stimulate glycodelin production from a developed endometrium. This is the first report of a nonsteroidal ovarian factor that controls glycodelin secretion, and these results suggest a function for relaxin during early pregnancy. Glycodelin is a potent inhibitor of sperm zona pellucida binding by virtue of its extensive carbohydrate structure, but it is normally at a nadir in the periovulatory period. The data demonstrate that relaxin can stimulate glycodelin secretion throughout the menstrual cycle, including the periovulatory period, when relaxin-induced glycodelin secretion could have a contraceptive effect.